Quantitative olfactory disorders and occupational exposure to phenolic resins - Matteo Riccó; Carlo Signorelli; Enrico Pistelli; Silvia Cattani (Nofer Institute of Occupational Medicine, 2016)
Background: To investigate whether exposure to phenolic resins (PR) is associated with quantitative olfactory disorders (QOD), a cross-sectional study of self-reported olfactory impairment (SROI) was performed in occupationally exposed subjects. Material and Methods: Sixty-six workers (45 males, 21 females) at the age (mean ± standard deviation) of 39.8±10.15 years old were divided into 3 exposure groups on the basis of biological exposure indices (BEI) for urinary phenols. It was asked whether the sense of smell has been normal or abnormal during the recent 2 months: the participants were eventually divided into self-reported normosmic, hyposmic, hyperosmic groups. Results: Prevalence of the SROI was 45.5%, with 21 (31.8%) workers complaining about the hyposmia, 12 (18.2%) - anosmia and 9 (13.6%) - hyperosmia. In univariate analyses, female sex was associated with the SROI and the hyperosmia. Highly exposed workers showed the SROI more frequently (odds ratio (OR) = 4.714; 95% confidence interval (CI): 1.077-20.626) than those not exposed (reference) or low exposed (OR = 1.333; 95% CI: 0.416-4.274). In multivariate analyses, female sex was the main risk factor for the SROI (adjusted odds ratio (ORa) = 5.622; 95% CI: 1.525-20.722) and the hyperosmia (ORa = 25.143; 95% CI: 2.379-265.7) but a high exposure to phenol (ORa = 11.133; 95% CI: 1.060-116.9) was the main risk factor for the anosmia. Conclusions: This study has found slight evidence among the cross-section of chemical industry workers that the exposure to phenol may be associated with the SROI. On the other hand, self-reporting of the QOD may be biased by personal factors and further research with objective measurement is therefore required. Med Pr 2016;67(2):173-186